2021
DOI: 10.1093/ejo/cjab065
|View full text |Cite
|
Sign up to set email alerts
|

Bone remodelling patterns around orthodontic mini-implants migrating in bone: an experimental study in rat vertebrae

Abstract: Summary Background Orthodontic implant migration has been clinically observed in presence of continuous loading forces. Recent studies indicate that osteocytes play a crucial role in this phenomenon. Objectives Aim of this study was to investigate local osteocytic gene expression, protein expression, and bone micro-structure in peri-implant regions of pressure and tension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…On the other hand, whole mini-implant displacement seems to reach mean levels of about 2.7 mm, with maximal values up to 5.5 mm [33,34]. Displacement seems to further relate to the intensity of the orthodontic loading-low forces broadly induce tipping, while high forces also induce displacement at the mini-implant head, with further alterations in the velocity of migration with time [18]. From a biological point of view, the immediate orthodontic loading may preclude the integration of the surrounding tissues with the implant surface, leading to localized resorption-as a mechanical reaction, given the viscoelastic properties of the bone [35].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, whole mini-implant displacement seems to reach mean levels of about 2.7 mm, with maximal values up to 5.5 mm [33,34]. Displacement seems to further relate to the intensity of the orthodontic loading-low forces broadly induce tipping, while high forces also induce displacement at the mini-implant head, with further alterations in the velocity of migration with time [18]. From a biological point of view, the immediate orthodontic loading may preclude the integration of the surrounding tissues with the implant surface, leading to localized resorption-as a mechanical reaction, given the viscoelastic properties of the bone [35].…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the obtained differences may relate to variations within the experimental design, including dissimilarities in the selected animal model, the characteristics of the used mini-implants, the force and loading protocols, the location of implantation, the period of evaluation, the methodology, and the characterization methodologies, among other variables. Regardless of the outcomes, it has been recently suggested that the stress induction at the mini-implant interface-in spite of the prevalence of tension or compression forces-may be the trigger for bone remodeling, further enhancing the appositional process, leading to enhanced bone formation [18]. At the molecular level, whether no significant differences were obtained regarding the osteocytic gene expression program, variations in the expression of CTSK-coding for cathepsin k, a protease acknowledged as a major marker of the osteoclastic activity [59]-and those of RUNX2 and SP7-coding for Runt-related transcription factor 2 and Osterix, respectively, two major transcription factors regulating the osteogenic program [59]-were obtained in a site-and time-dependent manner [18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations